Unravelling the Dynamics: Understanding Erosion-Led Vulnerabilities at Selected Locations of Sirajganj, Bangladesh (Social Science Review, 2025)
People differ in their ability to cope with risks and hazards, so identifying and protecting vulnerable groups in the case of riverbank erosion hazards generally reveals the current conditions of rural communities and provides an excellent insight into how vulnerabilities may progress in the future. In order to present a completer and more accurate picture of vulnerabilities and vulnerable groups, this article advocates for the identification of various vulnerability dimensions in studies of vulnerable populations in the erosion-prone Belkuchi upazila of Sirajganj through a mixed-method approach and using the Kobo toolbox. It then calls for systematic solutions to each vulnerability as a guiding principle in vulnerability reduction and risk management. This can assist national and local governments in tailoring guidelines, recruiting experts to address specific requirements, and communicating with vulnerable groups in a manner that acknowledges the diversity that may exist within those groups. Local people in the two selected unions are traditionally connected to agricultural activities over generations. However, with frequent riverbank erosion, much of the arable land has been swallowed up, and some parts are converted into residences or factories. During the rainy season, erosion is exacerbated, and a significant proportion of individuals in all communities experience long-term unemployment issues. As a result, many have taken up low-paying jobs like rickshaw pulling, brick field labor, daily labor, etc. When it comes to the economy, the ability of landless people to support themselves remains vulnerable, and out-migration is taking a serious shape there. It is crucial for authorities to develop income-generating activities for the erosion-affected people to improve the current situation. Engagement in locally based organizations, whether governmental or non-governmental, can enhance the existing situation. Practitioners and community leaders need to work together to protect the vulnerable homes and livelihoods of the local community from riverbank erosion by improving readiness and resilience.Social Science Review, Vol. 41(2), December 2024, pp. 247-264